Kulturni turizem in lokalno prebivalstvo na primeru mestne destinacije Ljubljana - Stubičar, Nina (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2022)
Cultural tourism is one of the oldest and most established forms of tourism, which is especially true for urban destinations like Ljubljana. In this paper we look at cultural tourism from the perspective of the local population. Using a questionnaire, we investigated what residents think about cultural tourism in Ljubljana, how much they use what it offers, what improvements they suggest, and what added value cultural tourism has for the city. Residents emphasized the positive contribution of cultural tourism to the city, even if it does not provide any particular benefits to residents in terms of cultural offer. As a contribution, they highlight in particular the liveliness of the city, its internationalization, i.e. the contact of residents with foreigners, and the added value for the economy, which also influences the general development of the city.
Keywords: cultural tourism; Geografija turizma; geography of tourism; kulturni turizem; Ljubljana; local inhabitants; lokalno prebivalstvo; mestni turizem; Slovenia; Slovenija; turistična geografija; urban tourism